A CENTURY OF NEWS DISCOURSE - Bell, Allan (International Journal of English Studies, 2003)
This paper traces the development of news discourse across the 20th century ihrough a case study ofthe coverage of three expeditions to the South Pole: Captain Scott in 1912, Sir Edmund Hillary in 1958, and Peter Hillary in 1999. The way the news about the three expeditions reached New Zealand media serves as a framework and an illustration to examine three related issues: how technology has changed the time and place dimensions of news delivery; the consequent and concomitant shifts in news presentation; and associated changes in how humans have understood time and place. News values remain the same at a broad level across the century, but different in detail. Nationalism is obtrusive, but its focus shifts. In news practice, the deadline and the scoop drive the news in al1 three periods, but the scooping medium shifts from press to radio to television. The lapse between an event and its reporting shrinks exponentially from months to hours to minutes. The design of newspaper front pages changes radically, and news language compresses. There are social impacts, with newsworthy figures receiving closer exposure and the audience being cast in a more voyeuristic role.